Fruit quality of jabuticaba progenies cultivated in a tropical climate of altitude. (17th October 2014) - Guedes, Mayara Neves Santos; Rufini, José Carlos Moraes; Azevedo, Alcinei Mistico; Pinto, Nísia Andrade Villela Dessimoni
Abstract : Introduction . The jabuticaba tree ( Myrciaria jabuticaba ) belongs to the Myrtaceae family and produces a small fruit, native to central, southern and southeastern Brazil.Materials and methods . Fruits of 25 progenies of the jabuticaba tree, grown in a tropical highland climate, were evaluated as to physical, physicochemical and chemical characteristics: weight, longitudinal and transverse diameters, pulp and peel yields, seed mass, number of seeds per fruit, pulp and peel moisture, soluble solids, titratable acidity, [soluble solids/titratable acidity] ratio, pH, flavonoids, and phenolic compounds. The experimental design was completely randomized, the treatments being the 25 jabuticaba tree progenies.Results . A significant effect among progenies was observed for all characteristics evaluated. The chemical composition showed that the jabuticaba peel has a high phenolic compound content, and considerable flavonoid content. These results indicate that there is variability for the characteristics analyzed, enabling the economic exploitation of jabuticaba tree fruits for in natura consumption and processing.Conclusions . The physical and chemical characteristics combined can be proposed as excellent tools to select superior progenies. The fruits of five progenies showed desirable characteristics for the in natura market, while fruits of five other progenies hold high concentrations of natural antioxidants and may be listed as excellent options for the food industry.